2022
DOI: 10.3390/pr10122637
|View full text |Cite
|
Sign up to set email alerts
|

Ternary Inclusion Complex of Sinapic Acid with Hydroxypropyl-β-cyclodextrin and Hydrophilic Polymer Prepared by Microwave Technology

Abstract: Sinapic acid (SA) is a poorly water-soluble substance which could result in poor bioavailability. The aim of this study was to determine the “hydroxypropyl β-cyclodextrin (HPβCD)” solubilization of SA in the presence of the auxiliary substance hydroxypropyl methylcellulose (HPMC) and to evaluate the ternary inclusion complex prepared by microwave technology. Phase-solubility profiles showed that HPβCD exhibited the greatest solubilizing effect on SA in the presence of HPMC. The enhanced rate of SA dissolution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 59 publications
(71 reference statements)
0
8
0
Order By: Relevance
“… 25 , 32 The slope value was smaller than 1, which denotes an inclusion complex with molecules in a 1:1 molar ratio (BRA: βCD). 26 The apparent stability constant, K1:1, was found to be 119.06 M −1 . Therefore, it can be said that BAR and βCD formed a stable inclusion complex at a 1:1 molar ratio.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“… 25 , 32 The slope value was smaller than 1, which denotes an inclusion complex with molecules in a 1:1 molar ratio (BRA: βCD). 26 The apparent stability constant, K1:1, was found to be 119.06 M −1 . Therefore, it can be said that BAR and βCD formed a stable inclusion complex at a 1:1 molar ratio.…”
Section: Resultsmentioning
confidence: 95%
“…These interaction with BAR were established by the cavity of βCD through intermolecular forces, confirming BAR’s incorporation inside the cavity of –CD. 26
Figure 1 Phase solubility plot of βCD and BAR.
…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Taupitz et al [94] confirmed enhancing of itraconazole solubility by forming ternary systems with polymer (Soluplus ® ) in a dry complex with cyclodextrin (HPβCD) or hydroxybutenyl-β-cyclodextrin (HBen-β-CD). Ahad et al [95] showed improved solubility of sinapic acid in water in the presence of HPβCD/HPMC. A similar observation was reported by El-Maradny et al [89] for the meloxicam-HPβCD-PVP complexes.…”
Section: Resultsmentioning
confidence: 99%
“…However, more research is needed to determine the optimal dose and long-term safety of SA supplementation. Also, SA has poor solubility in water, which limits its therapeutic efficacy and bioavailability [13]. A self-nanoemulsifying drug delivery system (SNEDDS) has been used to solve these problems.…”
Section: Introductionmentioning
confidence: 99%